Respuesta :
By the Binomial Theorem:
(a + b)^n = sum(k=0 to n) [C(n, k) * a^(n - k) * b^k].
By letting a = 2x, b = 3, and n = 9
(2x + 3)^9 = sum(k=0 to 9) [C(9, k) * (2x)^(9 - k) * 3^k].
As you can see, the power of x is 9 - k. Since we want the x^6 term:
9 - k = 6 ==> k = 3
Thus, letting k = 3 yields the term containing x^6 to be:
C(9, 6) * (2x)^(9 - 3) * 3^4 = 435456x^6.
.
(a + b)^n = sum(k=0 to n) [C(n, k) * a^(n - k) * b^k].
By letting a = 2x, b = 3, and n = 9
(2x + 3)^9 = sum(k=0 to 9) [C(9, k) * (2x)^(9 - k) * 3^k].
As you can see, the power of x is 9 - k. Since we want the x^6 term:
9 - k = 6 ==> k = 3
Thus, letting k = 3 yields the term containing x^6 to be:
C(9, 6) * (2x)^(9 - 3) * 3^4 = 435456x^6.
.